Curcumin attenuates high glucose‐induced inflammatory injury through the reactive oxygen species–phosphoinositide 3‐kinase/protein kinase B–nuclear factor‐κB signaling pathway in rat thoracic aorta endothelial cells. Issue 4 (12th December 2017) - Zhang, Zhen; Li, Keming
Abstract: Aims/Introduction: Endothelial cell inflammatory injury is likely required for barrier dysfunction under hyperglycemic conditions. Curcumin (CUR) is well known for its anti‐inflammatory effect. However, there have been few reports about the anti‐inflammatory effect of CUR induced by high glucose in endothelial cells. The aim of the present study was to investigate the inflammatory effect of high glucose and the anti‐inflammatory effect of CUR induced by high glucose in rat thoracic aorta endothelial cells (TAECs). Materials and Methods: Well characterized TAECs were established and cell viability was assayed by the cell counting kit‐8 method, messenger ribonucleic acid and protein expression were identified by real‐time polymerase chain reaction, western blot or enzyme‐linked immunosorbent assay, respectively. The production of reactive oxygen species was observed by a fluorescence microscope. Results: High glucose (30 mmol/L) significantly decreased the cell viability of TAECs after being co‐cultivated for 12 h and showed a time‐dependent manner, and increased interleukin (IL)‐1β, IL‐6 and tumor necrosis factor‐α secretion in TAECs. The injury effect of high glucose was involved in the reactive oxygen species–phosphoinositide 3‐kinase (PI3K)/protein kinase B (AKT)–nuclear factor (NF)‐κB signaling pathway. Anti‐oxidant N‐acetylcysteine, PI3K and NF‐κB‐specific pathway inhibitors can abolish the secretion of these inflammatory factors; pretreatment with anti‐oxidant N‐acetylcysteine significantly decreased PI3K expression, the level of phosphorylated AKT and nuclear NF‐κB; pretreatment of LY294002 can significantly decrease the NF‐κB level in nuclei. After treatment with CUR for 12 h, IL‐1β, IL‐6 and tumor necrosis factor‐α secretion were markedly decreased, and PI3K expression, the phosphorylation of AKT and nuclear NF‐κB level were also decreased. Conclusion: Curcumin attenuates high glucose‐induced inflammatory injury through the reactive oxygen species–PI3K/AKT–NF‐κB signaling pathway in rat thoracic aorta endothelial cells. Abstract : Curcumin attenuates high glucose‐induced inflammatory injury through ROS‐PI3K/AKT‐NF‐κB signaling pathway in rat thoracic aorta endothelial cells.